Evaluation of Developed (Integrated) Social Studies Textbooks in Light of Global Social Studies Standards - Al-Khawalda, Hamed Abdullah Suleiman; Tawalbeh, Hadi Mohammed (Journal of Posthumanism, 2025)
This study aims to evaluate the developed (integrated) social studies textbooks for the seventh and eighth grades in light of global standards for social studies. The study employs a descriptive methodology, and a questionnaire consisting of 46 items was developed, covering seven global standards. The questionnaire was distributed to a study population of 91 male and female teachers in the Qasabat Al-Mafraq Education Directorate. The results show that the degree of availability of global standards in the textbooks is high, with a mean score of (3.62) and a standard deviation of (0.60). The "Global Citizenship" standard ranks first with a high degree of availability, while the "Digital Tools and Artificial Intelligence" standard ranks last with a moderate degree of availability. The study recommends increasing the inclusion of technology and artificial intelligence concepts in the textbooks in line with global progress in these fields, while also enhancing the aspects related to standards with moderate availability to achieve a more comprehensive integration within the content of social studies.